Mydriatic Effect Of Tropicamide, Proparacaine And Lignocaine: A Mono And Combination Therapy - M.G.RAJANANDH; MATTA SAI PAVAN KUMAR.; VARUN CHAPARLA.; RAVI TEJA.; N.N.KALYAN CHAKRAVARTHI.; JOEL JOHNY MOLEKUNNEL; C.RAMASAMY (International Journal of Pharma and Bio Sciences, 2011)
The present study was undertaken to assess the mydriatic effect of mono and combination therapy of tropicamide with lignocaine in outpatients of Ophthalmology department. The proposed study was of prospective type. Ninety patients were included in the study. The study population was further subdivided into three individual groups of thirty each, in which all were assigned to receive the fixed regimens of tropicamide and combinations of tropicamide with lignocaine and proparacaine. The pupil dilatation with respect to tropicamide was found to be maximum at 6mm. The tropicamide and lignocaine regime produced more significant mydriatic effect at a maximum of 7mm in the outpatients, whereas the combination of tropicamide with proparacaine produced mydriasis as same as tropicamide alone. A new combination of tropicamide (muscarinic receptor antagonist) and lignocaine (local anesthetic) is found to be more effective in bringing about maximal dilatation of the pupil in ophthalmic patients who require routine screening.